(untitled) (diségno, 2026)
The so-called Temple of Venus at Baiae (2nd century A.D.) is one of the most extensive and complex surviving Hadrianic composite vaulted architecture. Although traditionally identified as a temple, the building was in fact part of the Baian thermal complex. Its spatial configuration reflects the experimental character typical of Hadrianic design. This study, based on an integrated survey, investigates the geometrical logic underlying its plan and elevation. The analyses focus on whether the composition was governed by a modular grid in plan and elevation, with diameters set as multiples of seven and articulated through the ad quadratum scheme. Reverse modelling protocols and best-fitting algorithms were applied to the polygonal model of the rotunda to test these hypotheses. The results confirm a design diameter of 91 pedes, with a modular subdivision of 13 pedes, consistent with other Hadrianic domes. In elevation, the vault appears as composite “umbrella” dome made up of alternating cylindrical segments and trikentron surfaces, creating a coherent vaulted system. The unusually slender proportions (1:8.86 diameter-to-thickness ratio) highlight the structural audacity of the monument. The research demonstrates how Hadrianic architecture employed flexible geometric tools, –multiples of seven, ad quadratum, and modular grids– not only for design efficiency but also to generate innovative spatial solutions. These findings contribute to the broader understanding of Hadrianic experimentation.